2022
DOI: 10.3390/en15093260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Air Flow on the Combustion Process and Preheating Effect of the Intake Manifold Burner

Abstract: Diesel engines show poor performance and high emissions under cold-start conditions. The intake manifold burner is an effective method to increase the intake air temperature and improve engine performance. In this paper, a visualization system was employed to investigate the combustion process of the intake manifold burner. The effects of diesel flow rate and airflow velocity on combustion performance were investigated. The combustion process of the intake manifold burner showed four stages: preparing stage A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…The combustion trend is in coherence with the BVE of fuel mixtures, projecting combustion efficiencies to respond positively to the increasing blending proportion of biodiesel, as shown in Figure 10. The increasing trend of blend efficiency is similar to that studied by Li et al (2022). The least burned fuel blend was B 5 with 54.5%, while B 100 had 81.47%, and D 100 had 88.06% at 0.0001125 kg/s or 75% loading capacity.…”
Section: Combustion Efficiency Outcomesupporting
confidence: 80%
See 1 more Smart Citation
“…The combustion trend is in coherence with the BVE of fuel mixtures, projecting combustion efficiencies to respond positively to the increasing blending proportion of biodiesel, as shown in Figure 10. The increasing trend of blend efficiency is similar to that studied by Li et al (2022). The least burned fuel blend was B 5 with 54.5%, while B 100 had 81.47%, and D 100 had 88.06% at 0.0001125 kg/s or 75% loading capacity.…”
Section: Combustion Efficiency Outcomesupporting
confidence: 80%
“…Researchers have also focused on the experimental and numerical dimensions of ICE flow. Increasing diesel and air flow rates in flame stability, combustion efficiency, and other parameters increased the combustion flame instability and efficiency (Li et al, 2022). An engine was studied as a twophase flow-accommodating entity for heat and fluid flow in CFD studies of velocity magnitude, penetration length, swirl and tumble ratios, and heat release rate, and an experimented heat flow characteristic in blends of 100% pure Khaya senegalensis biodiesel blend (B 100 ), B 20 , and pure diesel blend (D 100 ) of Jatropha biodiesel (Atgur et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In combustor A there is a regular increase in temperature along with the flow rate and Re at a constant equivalent ratio. If the air flow speed is greater, the combustion chamber temperature will be higher and the combustion rate will be faster, which will affect the fuel flow requirements in the system [20]. Combustor B has the same characteristics as combustor A.…”
Section: Calculation Of Reynolds Number (Re)mentioning
confidence: 99%
“…Moreover, compared with the standard preheating plug, increasing the length of the preheating part by 4mm can reduce the amount of CO, HC, NOX, and particulate matter emitted by 12.9%, 9.3%, 14.3%, and 9.8%, respectively, because with the increase in the glow plug length, the intake heating effect is further enhanced. For large diesel engines, using an intake air-heater to increase the intake temperature is another practical way to control emissions under cold start conditions [55]. Vivegananth and Ramesh [56] proposed a method to improve the cold start capability of low-compression ratio diesel engines by recompressing the intake air.…”
Section: Intake Heatingmentioning
confidence: 99%
“…The intake temperature of the diesel engine could be increased by installing an intake heater between the intake manifold and the turbocharger. The experimental results showed that the cold start For large diesel engines, using an intake air-heater to increase the intake temperature is another practical way to control emissions under cold start conditions [55]. Vivegananth and Ramesh [56] proposed a method to improve the cold start capability of lowcompression ratio diesel engines by recompressing the intake air.…”
Section: Intake Heatingmentioning
confidence: 99%